On the "Cal‐Mode" Correction to TOPEX Satellite Altimetry and Its Effect on the Global Mean Sea Level Time Series. Issue 11 (2nd November 2017) - Beckley, B. D.; Callahan, P. S.; Hancock, D. W.; Mitchum, G. T.; Ray, R. D.
Abstract: Comparison of satellite altimetry against a high‐quality network of tide gauges suggests that sea‐surface heights from the TOPEX altimeter may be biased by ±5 mm, in an approximate piecewise linear, or U‐shaped, drift. This has been previously reported in at least two other studies. The bias is probably caused by use of an internal calibration‐mode range correction, included in the TOPEX "net instrument" correction, which is suspect owing to changes in the altimeter's point target response. Removal of this correction appears to mitigate most of the drift problem. In addition, a new time series based on retracking the TOPEX waveforms, again without the calibration‐mode correction, also reduces the drift aside for a clear problem during the first 2 years. With revision, the TOPEX measurements, combined with successor Jason altimeter measurements, show global mean sea level rising fairly steadily throughout most of 24 year time period, with rates around 3 mm/yr, although higher over the last few years. Key Points: Tide‐gauge comparisons suggest TOPEX altimeter data have a small (±5 mm) U‐shaped 1 mm/yr drift Likely cause is an internal calibration‐mode range correction, corrupted by a degraded point target response Two revised altimeter time series show global mean sea level rising around 3 mm/yr for two decades, but recently increasing